Pengaruh Media Pembelajaran Flashcard Berbasis Digital Terhadap Hasil Belajar Membaca Permulaan Siswa Kelas I Sdn 04 Rasau Jaya - Emi Lestariani Emi Lestariani; Yunika Afryaningsih; Riyanti Nurdiana (Fakultas Pendidikan Islam dan Keguruan Universitas Garut, 2026)
This study aims to determine the effect of using digital-based flashcard media on the early reading achievement of first grade students at SDN 04 Rasau Jaya. This research employed a quantitative approach with a Quasi-Experimental method using a Nonequivalent Control Group Design. Early reading achievement was the dependent variable (Y), while digital-based flashcard media was the independent variable (X). The research population consisted of first grade students in classes A and B, with 19 students in each class.Class IA and Class IB functioned as the experimental and control groups, respectively. The sampling technique applied in this study was purposive sampling. The instruments used for data collection included observation sheets and tests. Based on the data analysis, differences were found between the posttest scores of the experimental and control groups. The average score of the control group was 77.89, while the experimental group had an average score of 86.77. Hypothesis testing was conducted using an independent sample t-test, as the normality test results indicated that the data were normally distributed. The independent sample t-test yielded a significance value of 0.049, which indicates that Ha is accepted. The results of this study demonstrate that digital-based flashcard learning media has a significant effect on students’ early reading achievement. Keywords: Early Reading Achievement, Digital-Based Flashcard Media